Experience co-creation of city visitors from the perspective of technological engagement - Mohd, Nur Shuhadah; Ismail, Hairul Nizam; Syed Jaafar, Syed Muhammad Rafy; Isa, Norliza (Institute of Physics Publishing, 2020)
The population today have immersed in mobile technology as ICTs is seen as capable in supplementing human social and psychological experience. Similarly, city visitors often perceived mobile technology as an inevitable partner in facilitating space consumption of an unfamiliar environment. Especially in urban setting, great incursion of technology in mediating human-destination encounter had manipulated visitor's cognitive conceptualisation process, and arguably critical for destination management and liveable city making. Due to high dependency on mobile assistance among current visitors market, cognitive stimulation from tech-human engagement was seen as influential force in psychologically motivating travel satisfaction and destination loyalty. Therefore, perspective on how visitor's cognitive experience affected by mobile engagement is critical in understanding the continuum of technology-mediated experience. The study was executed at Kuala Lumpur City Centre and the population was confined to millennial generation due to visibility as current tourism market. On-going survey of 235 respondents was conducted on 56 identified main attractions within the city centre. Preliminary findings reveal respondents’ desire towards deviation of smartphone engagement from daily uses during travel, as well as significant of interactive and value instilling engagement to uplift experience. This paper concluded with indication of research limitations and possible future research in this area.